Pengaruh Iklim Organisasi, Karakteristik Individu Dan Budaya Organisasi Terhadap Kinerja Karyawan Pada Koperasi Unit Desa (KUD) Pakis Malang - Maulidatul Karomah; Siti Asiyah; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to determine the effect of organizational climate, individual characteristics and organizational culture on employee performance at the Koperasi Unit Desa Pakis Malang. The sample used in this study were 33 employees of the Koperasi Unit Desa using the saturated sampling technique. The data analysis method used in this research is quantitative data analysis using descriptive statistical analysis and inferential statistics. The analysis used includes instrument testing, normality test, classical assumption test, multiple linear regression analysis, hypothesis testing and coefficient of determination using SPSS assistance.The results of this study indicate that simultaneously there is a significant influence between organizational climate, individual characteristics and organizational culture on employee performance at the Koperasi Unit Desa Pakis Malang. Meanwhile, partially it shows that the variables of organizational climate, individual characteristics and organizational culture have a significant effect on the performance of the employees of the Koperasi Unit Desa Pakis Malang. Keywords: Organizational Climate, Individual Characteristics and Organizational Culture on Employee Performance